A rational design of manganese electrocatalysts for Lewis acid-assisted carbon dioxide reduction. Issue 17 (12th April 2019) - Wang, Xiaoli; Ma, Haiyan; Meng, Caiyun; Chen, Dezhan; Huang, Fang
Abstract : Based on the mechanisms of CO2 electroreduction by Mn(mesbpy)(CO)3 Br, a formyl-substituted Mn complex is predicted to be a more effective electrocatalyst. Abstract : Herein, the mechanisms of Brønsted acid- and Lewis acid-assisted CO2 electroreduction by Mn(mesbpy)(CO)3 Br (1 ) were investigated by density functional theory calculations. Our results indicate that for the Lewis acid-assisted cycle, an energy sink (13 ) is present owing to the interaction between Mg(OTf)2 and activated CO2, which is disadvantageous to the apparent activation energy (Δ G ≠ ). Moreover, a series of substituted 13 counterparts were investigated to reduce the energy sink and decrease Δ G ≠ . Based on our study on the substituent effect, an excellent linear relationship was found between 2 e reduction potentials and LUMO energies of substituted 1, and a moderate linear relationship was observed between Δ G of substituted 13 and the 2 e reduction potential of substituted 1 counterparts. Moreover, for the CO2 reduction assisted by a Lewis acid, the formyl-substituted complex R8 has been predicted to be a more effective catalyst with lower overpotential and higher catalytic activity than its parent complex 1 .